Garment Industry in Cavite Export Processing Zone Working Conditions Survey - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
One of the purpose of many developing countries in establishing export processing zone is to provide jobs to the people especially those in rural areas, to increase their productivity and their individual and family income, and thereby improve the level and quality of their living condition.  This paper aims to assess the working lives and working conditions of garment industry in Cavite Export Processing Zone.  The respondents were selected by multistage random sampling from Lee Outfit Corporation to be representative of the working population in the company.  The results indicate that the working condition is good enough, but the wages is not enough compared to the high cost of living in the Philippines.  The key stakeholders and other actors concerned must work together to develop effective national policies to promote local economy and foster productive foreign investment and trade in the EPZs to prevent or mitigate adverse effects from the primary aim of setting up EPZs.